ANALISA KEBUTUHAN MEDIA PEMBELAJARAN IPAS BERBASIS PBL TERINTEGRASI NILAI TRI-NGA UNTUK SISWA SEKOLAH DASAR - Nawati, Anik; Ari Setiawan; Akbar Al-Masjid; Banun Havifah Cahyo Khosiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In primary education, character education is crucial as this period is the foundation for children's moral and ethical development. Natural Sciences and Social Sciences (IPAS) education in elementary schools aims to develop students' understanding of society and the social environment while instilling moral values. However, IPAS learning often faces challenges in student engagement. This study aims to analyze the needs of IPAS learning media based on Problem-Based Learning (PBL) integrated with Tri-Nga values (Ngerti, Ngrasa, Nglakoni) for elementary school students. This research adopts a descriptive qualitative approach with a case study method to analyze the needs of Student Worksheets (LKPD) media in IPAS learning based on PBL and Tri-Nga values. The results reveal challenges in IPAS learning, including a lack of student discipline and difficulties in teaching IPAS material that involves a lot of memorization. The implementation of LKPD based on PBL and Tri-Nga values is expected to help address these challenges and support the development of student discipline character.